Astigmatismo y miopía magna en paciente masculino de 14 años. - Mendoza Moran, Yaritzi Esther (2023)
The prevalence of high myopia is increasingly frequent today when it is not treated in time it can lead to blindness in those who suffer from it, the complications and their incidence make high myopia become a topic of general interest. There are several factors that affect the appearance of high myopia, including age, genetic factors and the ocular conditions that the patient presents, the main symptoms that the patient with high myopia presents are headache, visual fatigue, difficulty in focusing, difficulty in see at night. The treatments currently available are not preventive, they are palliative, that is, they allow us to keep track of the progress of this visual condition through regular check-ups and in certain cases, patients are also indicated to refer patients to an ophthalmologist in order to rule out other conditions. anomalies. In the present clinical case we have a 14-year-old male patient presenting myopia and astigmatism, in recent weeks he has indicated the following symptoms: headache, blurred vision and difficulty in night vision despite using an optical correction means in this case air lenses. Once the corresponding optometric checks were carried out, it was determined. CODING OF THE DIAGNOSIS ACCORDING TO ICD 10: Myopia: H52.1. The treatment is prescribed renewal of measures in aerial lenses, a follow-up with check-ups every 30 days in order to verify the evolution of the patient.